The Importance of Communication In The Family” Ali and The Queens of Queens” - Barlan Izzulhaq; Marudut Bernadtua Simanjuntak (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
This film tells about the poor communication relationship between a child and his parents. Lack of communication relationships, create prolonged misunderstandings. Lack of communication in the family makes relationships disharmonious, debates, and separation. This film is directed by Lucky Kuswandi and is the work of Gina S. Noer. Lack of communication also has a bad impact on a child's growth because it makes the child mentally disturbed. The debate between the parents occurs because of the lack of communication in family relationships. Lack of communication makes the child curious about what happened between his parents. Poor communication relationships create divisions in the long-established family, lack of communication also results in a loss of trust in each other. This film is very interesting for fans who like drama genre films. Conflicts about children whose mothers leave them abroad. The child was curious and finally he decided to follow his mother. This film takes place in the cities of Queens, New York, and Jakarta. This film won awards in 2021, namely the image trophy, the Bandung film festival award, and the Indonesian film festival. The method used in this study is a descriptive qualitative method to analyze the meaning of the communication relationship.